Diseño de la red de campus para el Centro de Formación Continua San Bartolo de la Universidad Politécnica Salesiana - Álvarez García, Luis Enrique (2018)
This technical project was prepared for the Centro de Formación Continua San Bartolo of the Universidad Politécnica Salesiana, in order to provide students, teaching and administrative staff, with a professional proposal that contemplates the design of a campus network based on a modern technological infrastructure that meets the needs of Internet connection and communication, offering an agile and secure connectivity experience. During the situational analysis of the property it was found that this center does not have any connectivity infrastructure; which is why we propose the design of a network based on the hierarchical business architecture of CISCO, ensuring that it allows a correct distribution in the sending and receiving of data, while providing a solution with high scalability and availability. For the elaboration of the design of the network, the standards of length of structured cabling and wireless networks were observed, which specify the minimum requirements that these components must fulfill, such as; length and type of cable, accessories and work areas; likewise, wireless coverage, minimum signal levels, data speed, work frequency, among others. The project also aims to optimize the use of resources and achieve a design that is adaptable to the changes that are made in terms of space distribution or advances in the technology of active and passive equipment. Finally, this document presents a set of plans with the physical and logical distribution of the network components, estimating a budget for the execution of the project.